Apmierinātības ar pāra attiecībām un vecāku kompetences izjūtas saistību atšķirības reģistrētās un nereģistrētās attiecībās - Vizbule, Eva (Latvijas Universitāte, 2014)
Pētījuma mērķis bija noskaidrot, vai pastāv saistība starp apmierinātību ar pāra attiecībām un vecāku kompetences izjūtu, vai pastāv šo saistību atšķirības mātēm un tēviem reģistrētās, nereģistrētās attiecībās. Pētījumā piedalījās 60 mātes un 60 tēvi vecumā no 21 – 43 gadiem. Pētījumā tika izmantotas 2 aptaujas: Apmierinātības ar attiecībām un Vecāku kompetences izjūtas skalas. Pētījuma rezultāti uzrādīja statistiski nozīmīgu saistību starp apmierinātību ar pāra attiecībām un vecāku kompetences izjūtu mātēm un tēviem reģistrētās un nereģistrētās attiecībās. Pētījuma rezultāti neuzrādīja statistiski nozīmīgu šo saistību atšķirību mātēm un tēviem reģistrētās un nereģistrētās attiecībās. Atslēgas vārdi: apmierinātība ar pāra attiecībām, vecāku kompetences izjūta, dzimums, attiecību statuss

The aim of the research was to determine the link between partners’ relationship satisfaction and parenting sense of competence, if there are differences between mothers and fathers in registered, not registered relations. The study included 60 mothers and 60 fathers aged 21 – 43. The study was based on 2 surveys: Index of Marital Satisfaction and The Parenting Sense of Competence scales. The results showed statistically significant correlation between partners’ relationship satisfaction and parenting sense of competence for mothers and fathers in registered and not registered relations. There are no statistically significant differences in correlation between partners’ relationship satisfaction and parenting sense of competence for mothers and fathers in registered and not registered relations. Key words: partners’ relationship satisfaction, parenting sense of competence, gender, relationship status
Interrelatedness of partners' relationship satisfaction and parenting sense of competence, differences between registred and not registred relations
Keywords: Psiholoģija